Komitmen Organisasi Karyawan Plate For Me Restaurant Bandung - Kusherdyana (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2017)
A growing phenomenon in the world of industry and organizations today are professionals tend to be more committed to the profession than the company where she worked. Employees who are committed to the profession does not necessarily refer to an organization, so that employees like this is always moving work elsewhere. This study aims to reveal the extent to which employees' organizational commitment in Plate for Me Restaurant Bandung. The method used in this research is descriptive method which seeks to describe the organizational commitment of employees in the Plate for Me Restaurant Bandung. The population in this study were all employees at Restaurant Bandung which amounted to 18 employees. Research data collection tool was a questionnaire / questionnaire, and literature study. The results show the organizational commitment of employees is quite good. The study produced several recommendations' to the Plate For Me Restaurant Bandung should be done to improve and enhance the commitment of employees, managers and supervisors are more concerned with the motivation and commitment of subordinates by giving delegates the responsibility and the utilization of the skills of subordinates. Management should demonstrate to subordinates that they know very well where this company will be taken, thus karyawanpun know the strength of the company in achieving its objectives to achieve success. Success is what can foster pride on the employee.